FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GEJALA ANEMIA PADA SISWA/I SDN MUSTIKAJAYA VII KOTA BEKASI TAHUN 2025 - Pratiwi, Sabrina Syifa; Rony Darmawansyah (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
Anemia can occur in all age groups, including school-aged children. If left unaddressed, anemia in children can have negative impacts, such as impairing cognitive development, intelligence, and immune function, and can also affect the menstrual cycle and future pregnancy phases in female students. This study aims to identify the factors associated with anemia symptoms at SDN Mustikajaya VII, Bekasi City, in 2025. This is a quantitative study using a cross-sectional design. The population consists of 4th and 5th-grade students at SDN Mustikajaya VII, Bekasi City, with a total sample of 167 students. The sampling technique used was stratified random sampling, utilizing questionnaires and observational results. Data analysis included univariate analysis using frequency distribution and bivariate analysis using the chi-square test. The univariate analysis results showed that 25.7% of students had anemia symptoms, 53.3% had good knowledge, 70.7% had no history of illness, 62.9% had good nutritional status, 70.7% had mothers with higher education, 55.7% had breakfast habits, and 41.3% frequently consumed tea. The bivariate analysis results indicated a significant relationship between knowledge (p = 0.017), mother’s educational background (p = 0.000), and breakfast habits (p = 0.000) with anemia symptoms among 4th and 5th grade students at SDN Mustikajaya VII, Bekasi City, in 2025. Keywords: Anemia, Symptoms, Factors, Elementary School Students